Molecular cloning and expression analysis of major histocompatibility complex class IIB gene of the Whitespotted bambooshark (Chiloscyllium plagiosum) - Ma, Qian; Su, Yong-Quan; Wang, Jun; Zhuang, Zhi-Meng; Tang, Qi-Sheng; 王军; 唐启升 (SPRINGER, 2013)
National Natural Science Foundation of China [40876080] Major histocompatibility complex (MHC) plays an important role in the immune response to antigenic peptides in vertebrates. In this study, the full length of MHC IIB cDNA was isolated from the Whitespotted bambooshark (Chiloscyllium plagiosum) by homology cloning, and the rapid amplification of cDNA ends polymerase chain reaction. As a result, the MHC IIB cDNA is 1,407 bp, which contains an open reading frame (ORF) of 831 bp encoding a protein of 276 amino acids. Furthermore, seven alleles of the complete MHC IIB ORF were detected and the variable sites were mainly located in the immunoglobulin-like (beta(2)) region. Tissue distribution analysis showed that MHC IIB can be detected in all the ten tissues examined, with the highest expression in the spleen and gill. Challenge of C. plagiosum with the pathogenic bacteria, Vibrio harveyi, resulted in significant changes in the expression of MHC IIB mRNA in the three immune-related tissues (gill, liver and spleen). These results show that the MHC IIB plays an important role in response to bacterial infection in elasmobranches.